Deveres de proteção e meio ambiente do trabalho saudável - Bertotti, Monique (2015)
This study analyzes the environment of healthy work and the State protection duties. Firstly, an approach related to Socio-Environmental State and its principles was done, which the aim was contextualize the work environment as part of the environment in a broad sense. Later, was researched about the environment fundamental in the Federal Constitution of 1988, as well as the option of constituent for extended anthropocentrism. The study sought to emphasize also the importance of the ecological dimension of human dignity and socio-environmental existential minimum. The relationship of environmental rights with the others fundamental rights, such as the right to life, the right to decent work, the right to personal integrity, the right to health and the social and environmental function of property, was also analyzed. As alternative to achieve decent work in a balanced work environment was presented the concept of green jobs, prepared by the International Labour Organization (ILO) and little discussed in Brazil. Finally, the State protection duties related to the work environment and the prohibition of insufficient protection were analyzed. Situations in which the state does not meet the protective duties or meet them insufficiently were presented: the lack of regulation of the right to protection in the face of automation and the right to additional painfulness, the jurisprudential understanding of the impossibility of cumulation of additional compensation and the non utilization of objective civil liability for environmental damage as basis in cases of occupational accidents and occupational diseases arising from poor environmental conditions of work. In conclusion, unfortunately, the problems caused through work environment to employees are not recognized as environmental imbalance consequences. The proof of the study conclusion is that the environmental standards are not used as grounds to justify the condemnation of entrepreneurs in accidents at work and occupational diseases caused by the terrible environmental conditions of work.